Embodiment Electoral Justice Through Reconstruction & Strengthening Women's Representation in Legislative Elections in Indonesia Following Constitutional Court Decision Number 128/PUU-XXIV/2026 - Boiziardi AS (UNES Journal of Swara Justisia, 2026)
Women's representation in general elections in a democratic country is an important instrument in the principle ofelectoral justice and inclusive democracy. The Republic of Indonesia has implementedaffirmative action for women through Law Number 7 of 2017 concerning General Elections in Article 245 concerning the representation of women in the list of legislative candidates of at least 30%. This norm is weakened in its implementation when this Article does not explain the further mechanism regarding strict sanctions in the event of a violation of the law, thus raising issues regarding the effectiveness of the norm. This study aims to analyze how the regulation of women's representation quotas before and after the Constitutional Court Decision Number 128/PUU-XXIV/2026 and its implications for the realization of women's representation.electoral justice in the Indonesian election system. This study uses a normative juridical method with a legislative approach, a case approach, a conceptual approach, and a comparative approach. The results of the study indicate that Article 245 of the Election Law before the Constitutional Court's decision wasimperfect lawbecause it only contains the obligation to fulfill the women's quota without clear legal consequences if violated. This condition results in low levels of compliance by political parties with affirmative action policies for women and has the potential to hinder the fulfillment of women's political rights. Following Constitutional Court Decision No. 128/PUU-XXIV/2026, the General Elections Commission (KPU) authorized the disqualification or exclusion of political parties from electoral districts that did not meet the quota of at least 30% women's representation. Therefore, this decision constitutes a form ofconstitutional enforcement which strengthens the protection of women's political rights while realizing the principleelectoral justice in the Indonesian election system.